Udowodnij tożsamość:
1) ctgα / ctgα + tgα = cos²α
2) cosα / 1 + sinα + 1 + sinα / cosα = 2 / cosα
Oblicz wartość wyrażenia:
1) cos(-1125⁰ )×ctg(-60⁰)×tg120⁰/sin(-1110⁰)×cos225⁰×ctg405⁰
2) sin(-(13/4 π))+cos7/3π-tg21/4π+ctg19/6π
Rozwiąż równanie:
4sin³x-4sin²x-3sinx+3=0
Rozwiąż nierówność:
2-3cosx/1-4cos²x>1 dla x∈(0;2π>

1

Odpowiedzi

2009-04-01T22:57:21+02:00
1) ctg a / (ctg a + 1/ctg a) = ctg a / (ctg^2 a + 1)/ ctg a = ctg^2 a / (ctg^2 a + 1) = (cos^2 a / sin^2 a) / ((cos^2 a /sin^2 a) + 1) = cos^2 a / (cos^2 a + sin^2 a) = cos^2 a

2) (cos a)/(1+sin a) + (1+sin a)/(cos a) = (cos^2 a + 1 +2sin a + sin^2 a)/(cos a)(1+sin a) = 2( 1 + sin a) / cos a(1 + sin a) = 2/cos a

1) cos(-45)cos(-60)tg(120)/sin(-30)cos(225)ctg(45) =
(√2/2 * 1/2 * -√3/3) / (√3/2 * -√2/2) = 1/3

2) sin(-5/4 π) + cos(π/3) - tg 5/4π + ctg 7/6π =
√2/2 + 1/2 - 1 -√3 = (√2-1-2√3)/2
Równanie:
4sin³x-4sin²x-3sinx+3=0
4sin²x(sin x - 1) + 3(1 - sin x) = 0
4sin²x(sin x - 1) = 3(sin x - 1)
Ablo sin x - 1 = 0 czyli sin x = 1 czyli x = 90 stopni, albo
4sin²x = 3, czyli
4 - 4cos²x = 3,
-4cos²x = -1
cos²x = 1/4
cos x = |1/2|
czyli x = (+-) π/3 + 2kπ, gdzie k jest liczbą całkowitą
albo x = (+-) 2π/3 + 2kπ, gdzie k jest liczbą całkowitą